Factores asociados al incumplimiento del control de crecimiento y desarrollo en niños menores de 5 años San Martín Junín, 2025 - Jimenez Palacios, Rosa María; Rosales Barzola, Dialeni Yanela (Universidad Privada de Huancayo Franklin Roosevelt, 2026)
El estudio tuvo como objetivo determinar los factores asociados al incumplimiento del Control de CRED en niños menores de 5 años en el Centro de Salud San Martín, 2025. Fue de tipo básico, con diseño no experimental de casos y controles, con una población de 127 madres y una muestra de 84 participantes seleccionados por muestreo no probabilístico. Resultados se identificaron como factores asociados: trabajo materno (OR=0,142; p=0,000), gastos del hogar (OR=4,462; p=0,001), costo de transporte (OR=4,706; p=0,000), condiciones laborales (OR=3,200; p=0,013), falta de beneficios laborales (OR=18,182; p=0,000), desconocimiento del CRED (OR=22,000; p=0,000), creencias erróneas (OR=13,000; p=0,000), tiempo de espera (OR=12,308; p=0,000), atención insuficiente (OR=6,600; p=0,000).Se concluye que factores económicos, cognitivos e institucionales se asocian significativamente al incumplimiento del CRED (OR>1; p<0,05).

The study aimed to identify the factors associated with non-compliance with CRED (Growth and Development Control) check-ups among children under 5 years of age at the San Martín Health Center in 2025. It was a basic research study utilizing a non-experimental case-control design, involving a population of 127 mothers and a sample of 84 participants selected via non-probability sampling. The results identified the following associated factors: maternal employment (OR=0.142; p=0.000), household expenses (OR=4.462; p=0.001), transportation costs (OR=4.706; p=0.000), working conditions (OR=3.200; p=0.013), lack of employment benefits (OR=18.182; p=0.000), lack of knowledge regarding CRED (OR=22.000; p=0.000), erroneous beliefs (OR=13.000; p=0.000), waiting times (OR=12.308; p=0.000), and insufficient care (OR=6.600; p=0.000). It is concluded that economic, cognitive, and institutional factors are significantly associated with non-compliance with CRED check-ups (OR>1; p<0.05).
Factors Associated with Non-Adherence to Growth and Development Monitoring in Children Under 5 Years of Age: San Martín, Junín, 2025
Keywords: Factores; incumplimiento; control; http://purl.org/pe-repo/ocde/ford#3.01.05